India and Global Climate Change : Perspectives on Economics and Policy from a Developing Country. - Toman, Michael A. (Earthscan, 2003)
Though the impact of climate change will most likely be greatest with the already poor and vulnerable populations in the developing world, much of the writing about the costs and benefits of different policies to reduce greenhouse gas (GHG) emissions is by Western scholars, working in advanced industrialized economies. Drawing the majority of its contributions from authors based at Indian universities and other research centers, India and Global Climate Change provides a developing world perspective on the debate. With a population of over one billion, and an economy that is undergoing substant.